EFFECTS OF PROBLEM-BASED LEARNING APPROACH ON PROBLEM-SOLVING SKILLS AND COOPERATIVE WORKING ABILITY OF EIGHTH-GRADE STUDENTS - Anantasuk, Nattawat (PEOPLE: International Journal of Social Sciences, 2019)
The purposes of this research were 1) to study the problem-solving skills of students who were taught using problem-based learning approach between pre-study and post-study and 2) to compare the cooperative working ability of the students who were taught using problem-based learning approach and 3) to compare students’ problem-solving skills with gain at 70%. The sample comprised 36 students of Navamindarajudis Matchim School, Muang District, Nakhon Sawan. The instruments used consisted of 4 teaching plans, a problem-solving skill test, and a cooperative working assessment form. The research was conducted for four weeks. The research design used was One-Group Pretest Posttest Design. The data were analyzed using t-test dependent.The research findings: 1. There was a significant increase in the problem-solving skills of the students at .05 after being taught using problem-based learning approach. 2. There was a significant increase in the cooperative working ability of the students at .05 after being taught by using problem-based learning approach. 3. There was a significant increase in students’ problem-solving skills at 86.11% which was more than the gain of 70%.